Framing health for land-use planning legislation: A qualitative descriptive content analysis. (January 2016) - Harris, Patrick; Kent, Jennifer; Sainsbury, Peter; Thow, Anne Marie
Abstract: Purpose and setting: Framing health as a relevant policy issue for other sectors is not well understood. A recent review of the New South Wales (Australia) land-use planning system resulted in the drafting of legislation with an internationally unprecedented focus on human health. We apply a political science approach to investigate the question 'how and to what extent were health and wider issues framed in submissions to the review?' Methods: We investigated a range of stakeholder submissions including health focussed agencies (n = 31), purposively identified key stakeholders with influence on the review (n = 24), and a random sample of other agencies and individuals (n = 47). Using qualitative descriptive analysis we inductively coded for the term 'health' and sub-categories. We deductively coded for 'wider concerns' using a locally endorsed 'Healthy Urban Development Checklist'. Additional inductive analysis uncovered further 'wider concerns'. Findings: Health was explicitly identified as a relevant issue for planning policy only in submissions by health-focussed agencies. This framing concerned the new planning system promoting and protecting health as well as connecting health to wider planning concerns including economic issues, transport, public open space and, to a slightly lesser extent, environmental sustainability. Key stakeholder and other agency submissions focussed on these and other wider planning concerns but did not mention health in detail. Health agency submissions did not emphasise infrastructure, density or housing as explicitly as others. Conclusions: Framing health as a relevant policy issue has the potential to influence legislative change governing the business of other sectors. Without submissions from health agencies arguing the importance of having health as an objective in the proposed legislation it is unlikely health considerations would have gained prominence in the draft bill. The findings have implications for health agency engagement with legislative change processes and beyond in land use planning. Highlights: We investigate how health was included in a comprehensive land use planning legislative review. We use political science to qualitatively analyse ideas in health and other stakeholders' submissions. Health stakeholders only explicitly included health. Health and other submissions included economic issues, transport, open space and sustainability. Health submissions did not emphasise infrastructure, density or housing compared to others.